A Comparison between Different Methods of Estimating Anaerobic Energy Production - Andersson, Erik P.; McGawley, Kerry (Frontiers in Physiology, 2018)
Purpose: The present study aimed to compare four methods of estimating anaerobic energy production during supramaximal exercise. Methods: Twenty-one junior cross-country skiers competing at a national and/or international level were tested on a treadmill during uphill (7°) diagonal-stride (DS) roller-skiing. After a 1-min baseline measure of VO2, a 4×4-min continuous submaximal protocol was performed followed by a 600-m time trial (TT). For the maximal accumulated O2 deficit (MAOD) method the VO2-speed regression relationship was used to estimate the VO2 demand during the TT, either including (4+Y, method 1) or excluding (4-Y, method 2) a fixed Y-intercept for baseline VO2. The gross efficiency (GE) method (method 3) involved calculating metabolic rate during the TT by dividing power output by submaximal GE, which was then converted to a VO2 demand. An alternative method based on submaximal energy cost (EC, method 4) was also used to estimate VO2 demand during the TT. Results: The GE/EC remained constant across the submaximal stages and the supramaximal TT was performed in 185 ± 24 s. The GE and EC methods produced identical VO2 demands and O2 deficits. The VO2 demand was ~3% lower for the 4+Y method compared with the 4-Y and GE/EC methods, with corresponding O2 deficits of 56 ± 10, 62 ± 10 and 63 ± 10 mL∙kg-1, respectively (P < 0.05 for 4+Y versus 4-Y and GE/EC). The mean differences between the estimated O2 deficits were -6 ± 5 mL∙kg-1 (4+Y versus 4-Y, P < 0.05), -7 ± 1 mL∙kg-1 (4+Y versus GE/EC, P < 0.05) and -1 ± 5 mL∙kg-1 (4-Y versus GE/EC), with respective typical errors of 5.3%, 1.9% and 6.0%. The mean difference between the O2 deficit estimated with GE/EC based on the average of four submaximal stages compared with the last stage was 1 ± 2 mL∙kg-1, with a typical error of 3.2%. Conclusions: These findings demonstrate a disagreement in the O2 deficits estimated using current methods. In addition, the findings suggest that a valid estimate of the O2 deficit may be possible using data from only one submaximal stage in combination with the GE/EC method.